Sunitinib impedes brain tumor progression and reduces tumor-induced neurodegeneration in the microenvironment - Hatipoglu, Gökce; Hock, Stefan; Weiss, Ruth; Fan, Zheng; Sehm, Tina; Ghoochani, Ali; Buchfelder, Michael; Savaskan, Nicolai E.; Eyüpoglu, Ilker Yasin (Cancer Science, 2015)
Malignant gliomas can be counted to the most devastating tumors in humans. Novel therapies do not achieve significant prolonged survival rates. The cancer cells have an impact on the surrounding vital tissue and form tumor zones, which make up the tumor microenvironment. We investigated the effects of sunitinib, a small molecule multitargeted receptor tyrosine kinase inhibitor, on constituents of the tumor microenvironment such as gliomas, astrocytes, endothelial cells, and neurons. Sunitinib has a known anti-angiogenic effect. We found that sunitinib normalizes the aberrant tumor-derived vasculature and reduces tumor vessel pathologies (i.e. auto-loops). Sunitinib has only minor effects on the normal, physiological, non-proliferating vasculature. We found that neurons and astrocytes are protected by sunitinib against glutamate-induced cell death, whereas sunitinib acts as a toxin towards proliferating endothelial cells and tumor vessels. Moreover, sunitinib is effective in inducing glioma cell death. We determined the underlying pathways by which sunitinib operates as a toxin on gliomas and found vascular endothelial growth factor receptor 2 (VEGFR2, KDR/Flk1) as the main target to execute gliomatoxicity. The apoptosis-inducing effect of sunitinib can be mimicked by inhibition of VEGFR2. Knockdown of VEGFR2 can, in part, foster the resistance of glioma cells to receptor tyrosine kinase inhibitors. Furthermore, sunitinib alleviates tumor-induced neurodegeneration. Hence, we tested whether temozolomide treatment could be potentiated by sunitinib application. Here we show that sunitinib can amplify the effects of temozolomide in glioma cells. Thus, our data indicate that combined treatment with temozolomide does not abrogate the effects of sunitinib. In conclusion, we found that sunitinib acts as a gliomatoxic agent and at the same time carries out neuroprotective effects, reducing tumor-induced neurodegeneration. Thus, this report uncovered sunitinib's actions on the brain tumor microenvironment, revealing novel aspects for adjuvant approaches and new clinical assessment criteria when applied to brain tumor patients.
EVALuna2:22836